2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33209
|View full text |Cite
|
Sign up to set email alerts
|

Project-based Robotics Courses for the Students of Mechanical Engineering Technology

Abstract: received his Ph.D. from the City University of New York in 1995. He is currently the program director of a mechatronics project in the New York City College of Technology/CUNY. For the past 15 years, Dr. Zhang has been working on bringing mechatronics technology to the undergraduate engineering technology curricula, on creating internship programs for the college students through collaboration with Brooklyn Navy Yard Development Corporation, and on helping high school students to learn mechatronics through var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recently, there has been a push to incorporate AI and machine learning into the middle school and high school curriculum ( Xiong, Wang & Huang, 2018 ; Zhai et al, 2021 ; Dai et al, 2020 ; Knox, 2020 ; Ali et al, 2019 ). Project-based learning in robotics has been successful at the university level ( Zhang et al, 2020 ) and both game- and project-based learning have been shown to be effective in teaching students about AI ( Leitner et al, 2023 ; Martins & Wangenheim, 2022 ). Guiding students through projects involving image recognition is an excellent way to introduce them to the basics of machine learning and prepare them for a world that is quickly integrating AI into everyday life ( Sophokleous et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a push to incorporate AI and machine learning into the middle school and high school curriculum ( Xiong, Wang & Huang, 2018 ; Zhai et al, 2021 ; Dai et al, 2020 ; Knox, 2020 ; Ali et al, 2019 ). Project-based learning in robotics has been successful at the university level ( Zhang et al, 2020 ) and both game- and project-based learning have been shown to be effective in teaching students about AI ( Leitner et al, 2023 ; Martins & Wangenheim, 2022 ). Guiding students through projects involving image recognition is an excellent way to introduce them to the basics of machine learning and prepare them for a world that is quickly integrating AI into everyday life ( Sophokleous et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous benefits of active methodologies, the vast majority of these methods are currently applied in primary and secondary schools [31]. There are some cases where active methodologies are implemented in university studies [16,32,61,81,86,112]. However, it should be noted that applying a single active learning method (e.g., only project-based learning), may not be sufficient to achieve high levels of student motivation and commitment.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand just how much time is to be allocated for the course tasks, Table 3 provides the given weeks across the semester and when assignments are due. • Final presentation/competition This proposed curriculum is in its early stages, where like many education research in mechatronics lab curriculum a course survey is to be provided for feedback in order to gauge our success [22]. This proposed survey will allow analysis for how much students learned from the course, how engaged they were, and if they felt amount of material learned was reasonable.…”
Section: Course Timeline and Learning Skillsmentioning
confidence: 99%